2023
DOI: 10.1002/glr2.12058
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction of seasonal forage yield in perennial ryegrass

Agnieszka Konkolewska,
Steffie Phang,
Patrick Conaghan
et al.

Abstract: BackgroundGenomic selection has the potential to accelerate genetic gain in perennial ryegrass breeding, provided complex traits such as forage yield can be predicted with sufficient accuracy.MethodsIn this study, we compared modelling approaches and feature selection strategies to evaluate the accuracy of genomic prediction models for seasonal forage yield production.ResultsOverall, model selection had limited impact on predictive ability when using the full data set. For a baseline genomic best linear unbias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…They demonstrated that glycosyl hydrolase family 16 xyloglucan endotrans-glycosylase was included in brassinolide hormone biosynthesis and pathways. Besides, Konkolewska et al (2023) mentioned that the glycosyl hydrolase family 16 xyloglucans are intricate hemi-cellulosic polysaccharides that undergo biosynthesis within the Golgi apparatus before being transported to the cell wall of alfalfa. These molecules play essential roles in processes such as cell growth and expansion, energy metabolism, and signaling.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that glycosyl hydrolase family 16 xyloglucan endotrans-glycosylase was included in brassinolide hormone biosynthesis and pathways. Besides, Konkolewska et al (2023) mentioned that the glycosyl hydrolase family 16 xyloglucans are intricate hemi-cellulosic polysaccharides that undergo biosynthesis within the Golgi apparatus before being transported to the cell wall of alfalfa. These molecules play essential roles in processes such as cell growth and expansion, energy metabolism, and signaling.…”
Section: Discussionmentioning
confidence: 99%